Preparation of Hierarchically Assembled Silver Nanostructures based on the Morphologies of Crystalline Peptide‐Silver(I) Complexes. Issue 3 (14th March 2019) - Miyake, Ryosuke; Nitanai, Yukari; Nakagawa, Yuki; Xing, Junfei; Harano, Koji; Nakamura, Eiichi; Okabayashi, Jun; Minamikawa, Takeo; Uruma, Keirei; Kanaizuka, Katsuhiko; Kurihara, Masato
Abstract: The preparation of a hierarchically assembled Ag nanostructures based on a nanocrystalline assembly was demonstrated using an Ag(I) complex of a dipeptide (AspDap). By heating under N2 gas, a spherical assembly of a nanocrystalline dipeptide‐Ag(I) complex (diameter 4–5 μm), which has a morphology similar to the assembled structure of the dipeptide, was transformed to an assembly of Ag nanostructures, where the micrometre‐order crystalline morphology was maintained. In addition, detailed scanning electron microscopy studies revealed that Ag nanoparticles (diameter ca. 10 nm) were formed on the surface of the Ag nanostructure. When the Ag(I) ions were reduced to Ag(0), this phenomenon exhibited surface dependence due to the anisotropic two‐dimensional Ag(I) arrangement in the crystals. Thermogravimetric measurements and X‐ray photoelectron spectroscopy revealed that the reduction proceeds in a stepwise manner around 200–250 °C, together with the removal of primary and secondary carboxylic groups in the dipeptide. Comparison with the heating process of the crystalline Ag(I) complex of β‐alanine indicated that stepwise reduction is key for maintaining the original micrometre‐order morphology. Abstract : A silver lining : The preparation of hierarchically assembled Ag nanostructures based on a nanocrystalline assembly was demonstrated using a Ag(I) complex of a dipeptide (AspDap). Stepwise reductions of the Ag(I) centre and protection by amino residues, which both result from the dipeptide, are key for maintaining the original crystalline morphology.